2003
DOI: 10.1103/physrevlett.91.063201
|View full text |Cite
|
Sign up to set email alerts
|

H+H2Thermal Reaction: A Convergence of Theory and Experiment

Abstract: New experimental and theoretical rate constants for two isotopologs of the simplest chemical reaction, H+H2-->H2+H, are presented. The theoretical results are obtained using accurate quantum dynamics with a converged Born-Oppenheimer potential energy surface and include non-Born-Oppenheimer corrections. The new experiments are carried out using a shock tube and complement earlier investigations over a very large T range, 167 to 2112 K. Experiment and theory now agree perfectly, within experimental error, bring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 50 publications
3
83
0
Order By: Relevance
“…Recent studies have demonstrated that computational techniques employing advanced treatments for both electronic and nuclear motion problems have the ability to rival the accuracy of experimental data [13][14][15]. These studies all employed convergent hierarchies of basis sets and correlation methods to solve the electronic structure problem.…”
Section: Potential Energy Surface Calculationsmentioning
confidence: 99%
“…Recent studies have demonstrated that computational techniques employing advanced treatments for both electronic and nuclear motion problems have the ability to rival the accuracy of experimental data [13][14][15]. These studies all employed convergent hierarchies of basis sets and correlation methods to solve the electronic structure problem.…”
Section: Potential Energy Surface Calculationsmentioning
confidence: 99%
“…Such risk is even greater if the model is used for extrapolation. The final triumph of the first principles approach to the reaction H + H 2 → H 2 + H, occur only came in 2003 when Mielke and colleagues [35] presented a new constants of experimental and theoretical speeds. The theoretical calculations were obtained using quantum dynamics in an exact adiabatic potential surface including Born-Oppenheimer corrections.…”
Section: The Origin Of Quantum Chemistry Methodsmentioning
confidence: 99%
“…As pointed out by Mielke et al [1], there is a very limited set of 'solved problems' in molecular quantum mechanics. These problems all involve small, few-electron hydrogenic systems.…”
Section: Introductionmentioning
confidence: 99%